Полет: (записки художника) / В. Л. Белых - Белых Валентин Леонидович (Удмуртия, 2016)
Экземпляры: ф.15 (20200120) / Инвентарный номер: 59927 / Цена: / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: Б 43 / ГРНТИ: 18.31.31 / ББК: 85.143(2Рос.Удм)